2012
DOI: 10.9753/icce.v33.currents.25
|View full text |Cite
|
Sign up to set email alerts
|

Low Frequency Wave Resonance in Fringing Reef Environments

Abstract: Low frequency wave resonance has been postulated to enhance damage to coral reef protected coastlines during storm events. This paper uses the numerical model XBeach to examine the dynamics that contribute to resonance that have been previously observed on a fringing reef on Guam during tropical storm Man-Yi (Péquignet et al., 2009). The methods to identify resonance in numerical (or field data) are comprehensively reviewed with three indicators of resonance proposed based upon data obtained at two locations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…It would appear that in Puerto Morelos the width of the reeflagoon has a greater influence on the resonant periods than the water depth (W = 460 m at P0; see Table 1). This is in agreement with results presented by Pomeroy (2011). …”
Section: Infragravity Wave Energysupporting
confidence: 83%
“…It would appear that in Puerto Morelos the width of the reeflagoon has a greater influence on the resonant periods than the water depth (W = 460 m at P0; see Table 1). This is in agreement with results presented by Pomeroy (2011). …”
Section: Infragravity Wave Energysupporting
confidence: 83%
“…This resonant forcing and VLF patterns over the Ipan reef were found to be caused by the modulation of breaking swell waves at the reef crest [ Péquignet et al ., ]. A subsequent modeling study based on the Ipan observations found that the forcing of resonant modes over this reef was dependent on not only the increase in water levels due to the storm event, but also the frictional characteristics of the reef flat; dissipation due to bottom friction counteracts the excitation of resonant frequencies by dampening the amplification peaks at the shoreline [ A. W. M. Pomeroy et al ., ]. Thus, for a given reef geometry and water depth, one would expect smoother, lower relief reefs, such as Roi‐Namur, to be subject to greater shoreline amplification due to resonance modes.…”
Section: Discussionmentioning
confidence: 99%
“…In this region, low-frequency waves (i.e., infragravity waves with periods 25-250 s) are generated by the breaking of incident high-frequency waves (Péquignet et al, 2014;Pomeroy et al, 2012a). In some cases low-frequency wave motions with periods even larger than the infragravity band (i.e., periods exceeding 250 s) can also be generated at the natural (seiching) frequency of coral reef flats, which may also be resonantly forced by incident wave groups (Péquignet et al, 2009;Pomeroy et al, 2012b). This disparity between high and low-frequency waves often results in a bimodal spectrum of wave conditions on coral reef flats and lagoons, where wave energy is partitioned between distinct high-frequency (sea-swell) and low-frequency (infragravity) wave bands (Pomeroy et al, 2012a;Van Dongeren et al, 2013).…”
Section: Introductionmentioning
confidence: 98%